2010
DOI: 10.1002/adfm.201001058
|View full text |Cite
|
Sign up to set email alerts
|

Heteroepitaxial Patterned Growth of Vertically Aligned and Periodically Distributed ZnO Nanowires on GaN Using Laser Interference Ablation

Abstract: A simple two‐step method of fabricating vertically aligned and periodically distributed ZnO nanowires on gallium nitride (GaN) substrates is described. The method combines laser interference ablation (LIA) and low temperature hydrothermal decomposition. The ZnO nanowires grow heteroepitaxially on unablated regions of GaN over areas spanning 1 cm2, with a high degree of control over size, orientation, uniformity, and periodicity. High resolution transmission electron microscopy and scanning electron microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 28 publications
0
37
0
Order By: Relevance
“…Other than that, based on laser interference, two-dimensional (2D) [290] or 3D [291] periodic structures could be generated by so-called laser interference lithography. The periodically distributed high intensity of light physically burned off the polymer mask layer [292,293] or the substrate itself [294], which was used to pattern the growth of ZnO nanowire arrays. For example, in a study by Wei et al [293], the nanowire growth method followed what had been previously reported [48,91].…”
Section: Interference Lithographymentioning
confidence: 99%
“…Other than that, based on laser interference, two-dimensional (2D) [290] or 3D [291] periodic structures could be generated by so-called laser interference lithography. The periodically distributed high intensity of light physically burned off the polymer mask layer [292,293] or the substrate itself [294], which was used to pattern the growth of ZnO nanowire arrays. For example, in a study by Wei et al [293], the nanowire growth method followed what had been previously reported [48,91].…”
Section: Interference Lithographymentioning
confidence: 99%
“…Several strategies have been proposed to fabricate highly ordered ZnO NAs, such as nanosphere lithography (NSL) [64][65][66][67][68], electron beam lithography (EBL) [69][70][71][72], optical lithography (OL), and laser interference lithography (LIL) techniques [73][74][75][76][77][78][79][80]. Among these, self-assembled NSL is a simple and economical technique, which employs twodimensional (2D) self-assembled nanometer-sized polystyrene spheres as lithography masks to fabricate patterned arrays [64].…”
Section: Synthetic Methodologies and Properties For Patterned Zno Nasmentioning
confidence: 99%
“…(1). For patterned growth on GaN, laser interference ablation was used [87]. For patterning larger areas (rather than controlling density and size of individual nanorods, photolithography can be used [57,90,110].…”
Section: Growth Methodsmentioning
confidence: 99%
“…Also, while electron beam lithgraphy enables preparation of sufficiently small patterns, it may still be necessary to optimize growth parameters, such as temperature, to avoid growth of multiple nanorods from a single seed island [127]. (2), which could be grown over areas as large as 1 cm 2 [87]. Monolayers of colloidal crystals [125] can also be used for large area patterning.…”
Section: Growth Methodsmentioning
confidence: 99%